Isolation and Characterization Compounds From Hexane and Ethyl Acetate Fractions of Peperomia pellucida L. - Sri Hartati; Marissa Angelina; Indah Dewiyanti; Lia Meilawati (Journal of Tropical Life Science, 2015)
Peperomia pellucida was used traditionally in Indonesia for health treatment: wounds, boils, pimples, abscesses, abdominal pain, colic, gout, kidney, rheumatic pain, fatigue headache, furuncles, conjunctivitis and anti dermatogenic and also for dengue treatment. The isolation compounds from hexane and ethyl acetate fractions of Peperomia pellucida L. are conducted by maceration of the dry herbs sample with methanol and partition with hexane, ethyl acetate, butanol and water.The hexane and ethyl acetate fractions were fractionated by gravitation column chromatography and eluted successively with hexane, ethyl acetate and methanol by the gradient. The structure was elucidated base on spectroscopy data of NMR proton and carbon for one and two dimension, LC-MS and FT-IR. The isolation founded three compounds are stigmasterol, analogue of pheophytin and b-sitosterol-D-glucopyranoside.